2021
DOI: 10.1039/d1ta00232e
|View full text |Cite
|
Sign up to set email alerts
|

Induced crystallization of sol–gel-derived zinc oxide for efficient non-fullerene polymer solar cells

Abstract: With the rapid development of near-infrared absorbing acceptor materials, the photoelectric conversion efficiency of polymer solar cells (PSCs) has been greatly improved in the past several years. However, serious charge...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…There are various methods for synthesizing ZnO nanomaterials; the conventional means include the hydrothermal method [ 28 ], electrochemical deposition [ 29 ], magnetron sputtering deposition [ 30 ] and chemical vapor deposition [ 31 ], as well as sol-gel process [ 32 ]. Table 1 shows the comparison of some synthetic methods of ZnO nanomaterials.…”
Section: Zno Nanostructures and Synthetic Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are various methods for synthesizing ZnO nanomaterials; the conventional means include the hydrothermal method [ 28 ], electrochemical deposition [ 29 ], magnetron sputtering deposition [ 30 ] and chemical vapor deposition [ 31 ], as well as sol-gel process [ 32 ]. Table 1 shows the comparison of some synthetic methods of ZnO nanomaterials.…”
Section: Zno Nanostructures and Synthetic Methodsmentioning
confidence: 99%
“…The sol-gel method is suitable for the synthesis of zero-dimensional ZnO nanomaterials, in which the Zn-containing compounds are dissolved by a solution and the sol system is formed after chemical reaction, then transformed into a gel system. Finally, after dehydration and heat treatment, ZnO nanoparticals are produced, which possess high purity and uniform distribution and the particle size of which is controllable [ 32 ]. However, the complex reactions, various variables and long process time are the disadvantages of this method, which seriously affect the performance of ZnO products.…”
Section: Zno Nanostructures and Synthetic Methodsmentioning
confidence: 99%
“…Employing ZnO film as an efficient electron transport layer, a power conversion efficiency of 16.62 % was afforded in inverted OSCs. [62] Metal elements doping is used to adjust the optoelectronic and morphological properties of the ZnO layer. Yang et al reported the Kpresenting ZnO interface induces vertical phase separation of an active layer incorporating the non-fullerene acceptor IT-4F, which significantly improves the PCE of OSCs based on the Kpresenting ZnO interface.…”
Section: Electron Collection Interface Layermentioning
confidence: 99%
“…To reduce these drawbacks, different strategies have been reported in the literature, such as introducing different kinds of organic and inorganic dopants, processing with optimized solvents, and tuning the thermodynamic process of the film. 44–48 A state-of-the-art review providing the surface modification of ZnO with tuned electronic properties and improved device performance has been summarized by Hewlett and McLachlan in 2016. 42 Hence, we mainly summarize representative studies since then in this part.…”
Section: Metal Oxide-based Hybrid Cilsmentioning
confidence: 99%